KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 33 PADANG - Monika, Monika; Afnita, Afnita (Universitas Negeri Padang, 2019)
ABSTRACT There are three aims of this study. First, describe the skills of reading comprehention of VII grade students at SMP Negeri 33 Padang. Second, describe the writing skills of the report observation text of VII grade students at SMP Negeri 33 Padang. Third, describe the correlation of reading comprehention with the writing skills of the report observation text of VII grade students at SMP Negeri 33 Padang. The type of this research is quantitative in terms of descriptive methods. The design used in this study is correlational design. The population of this study was the seventh grade students of the SMP Negeri 33 Padang which was registered in the 2018/2019 school year, it was 192 students. The sample in this study was determined by proportional random sampling of 20% of the population, namely 36 students. The research data is in the form of scores on the skills test results of reading comprehention and scores on the results of the test writing skills of the report observation text. The instrument of this study is an objective test to measure reading comprehention skills and performance tests to measure report observation text writing skills. The results of this study are three. First, the skills to write report observation texts of VII grade students of the SMP Negeri 33 Padang is in accordance with the Good qualifications (B) with an averange value 82,99. Second, the skill of reading comprehention of VII grade students of the SMP Negeri 33 Padang in accordance with Good qualifications (B) with an averange value 81,42. Third, there is a significant correlation betwen reading comprehention skills and report observation text writing skills of VIII grade students of the SMP Negeri 7 Padang on n-1 freedom degrees and 95% significant level. H0 is reject and H1is accepted because the tcount is greater than ttable (13,59 > 2,68). Kata Kunci: Korelasi, Keterampilan Membaca Pemahaman, Keterampilan Menulis Teks Laporan Hasil Observasi.